The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1371/journal.pcbi.0030069
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Power to Detect Causal Associations by Combining Genotypic and Expression Data in Segregating Populations

Abstract: To dissect common human diseases such as obesity and diabetes, a systematic approach is needed to study how genes interact with one another, and with genetic and environmental factors, to determine clinical end points or disease phenotypes. Bayesian networks provide a convenient framework for extracting relationships from noisy data and are frequently applied to large-scale data to derive causal relationships among variables of interest. Given the complexity of molecular networks underlying common human diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
200
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(211 citation statements)
references
References 39 publications
2
200
1
4
Order By: Relevance
“…Phenomics has a chance of changing how we view heritable diseases first by defining latent phenotypes that underlie genetically similar phenotype categories and second by revealing unexpected genetic links among disease entities. (75) The incorporation of genetic data clearly improves the quality of the predictions over those derived solely from trait correlations, (76) although phenotypic overlap is often a very good predictor of functional relatedness of the underlying genes. (77) Thus van Driel and colleagues (78) found that similarity between phenotypes did correlate positively with several measures of gene function, including relatedness at the level of protein sequence, protein motifs, functional annotation, and direct protein-protein interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Phenomics has a chance of changing how we view heritable diseases first by defining latent phenotypes that underlie genetically similar phenotype categories and second by revealing unexpected genetic links among disease entities. (75) The incorporation of genetic data clearly improves the quality of the predictions over those derived solely from trait correlations, (76) although phenotypic overlap is often a very good predictor of functional relatedness of the underlying genes. (77) Thus van Driel and colleagues (78) found that similarity between phenotypes did correlate positively with several measures of gene function, including relatedness at the level of protein sequence, protein motifs, functional annotation, and direct protein-protein interaction.…”
Section: Discussionmentioning
confidence: 99%
“…From a statistical perspective, one can use the results of an eQTL study to prioritize a list of disease-associated loci to follow up on; that is, one can use the existence of a SNP-gene-expression association as prior evidence that variation at the locus is more likely to have disease consequences (2,6). Furthermore, eQTL studies can infuse causal information into gene-gene and protein-protein correlation networks by making use of the fact that DNA can affect gene expression, but not the other way around (1,(7)(8)(9). Finally, the utility of eQTL studies is likely to increase as larger and more diverse datasets are amassed, and with the advent of new technologies such as RNA sequencing and exon arrays (2).…”
mentioning
confidence: 99%
“…Bayesian network reconstruction (11, 12) is a powerful approach for simultaneously considering thousands of molecular or clinical variables and for identifying patterns of causal relationships between these variables in a completely data-driven fashion. We developed a way to overcome the chief limitation of this approach-deriving predictive models from correlation data (11,12,35)by leveraging DNA variation as a systematic source of perturbation (32). The resulting probabilistic causal networks are critical for understanding the behavior of any one gene in the context of human disease, because individual genes operate in molecular networks that define disease-associated biological and pathological events.…”
Section: New Medicinementioning
confidence: 99%